Характеристика механизмов антиульцерогенного действия ванилоидных рецепторов (TRPV1) на модели гастропатии, индуцированной ацетилсалициловой кислотой - Гладких, Ф.В. (Фармация и фармакология. 2017. Т. 5, № 3. С. 283–301., 2017)
Relevance. One of the main problems of the use of acetylsalicylic acid (ASA) is its withdrawal or initial "non-prescription" resulted by the developed or potential side effects on the side of the gastrointestinal tract. In this case, the reasons for the abolition of ASA are not only serious complications in the form of gastrointestinal bleeding or perforations, but also dyspeptic phenomena against the background of the development of aspirin-induced gastroenteropathy. Purpose of the study. To characterize the mechanisms of antiulcerogenic action of agonist TRPV1 (transient receptor potential vanilloid 1) vanillin (100 mg/kg) on the model of subchronic ASA-induced gastropathy in rats. Materials and methods. The study was performed on 35 mature male rats. Gastropathy induced by ASA was simulated by a five-day intragastric (i.g.) introduction via the orogastric probe of an ASA suspension of 150 mg/kg/day. Omeprazole (50 mg/kg, i.g.) and vanillin (100 mg/kg, i.g.) were administered as suspensions in 60 minutes. up to ASA. In the homogenates of the gastric mucosa, the concentration of malonic dialdehyde was determined (Stalnaya I.D. et al.) and catalased activity (Karolyuk MA et al.). The prooxidant/antioxidant ratio (ProAntidex) was calculated from the ratio of catalase activity (mcat/kg) and MDA concentration (umol/kg). The content of NO metabolites in the stomach tissues was determined by the method of Miranda K.M. Et al. Results and their discussions. Preventive prophylactic use of vanillin (100 mg/kg) leads to decrease in the intensity of processes of lipid peroxidation in the coolant caused by the action of ASA (150 mg/kg). This was indicated by a statistically significant (p≤0.05) decrease in MDA content by 26.4% and an increase in catalase activity by 29.0% relative to those of animals with ASA-induced gastropathy without correction. Also, the use of vanillin resulted in a statistically significant (p≤0.05) increase in the content of NO metabolites by 68.0% (841.4 ± 35.95 umol / g) relative to the animals in the control group. With combined use of vanillin and omeprazole, a statistically significant (p≤0.05) absolute normalization of the NO metabolite level (927.4 ± 34.78 mmol/g) in the coolant was established, which corresponded to the indices of intact animals.
Гладких Ф. В. Характеристика механизмов антиульцерогенного действия ванилоидных рецепторов (TRPV1) на модели гастропатии, индуцированной ацетилсалициловой кислотой. Фармация и фармакология. 2017. Т. 5, № 3. С. 283–301. DOI: http://dx.doi.org/10.19163/2307-9266-2017-5-3-283-301.
Keywords: TRPV1; гастропротектор; acetylsalicylic acid; ulcerogenicity; nitric oxide; NO